Long-term control of melanoma adrenal metastasis treated with radiotherapy. Issue 3 (7th March 2022) - McCann, Brendan; Higgins, Martin; Kok, David L.; Hong, Wei; Alipour, Ramin; Chua, Margaret S. T.
Abstract : Melanoma remains a large global burden with a significant proportion of patients succumbing to metastatic disease. The adrenal gland is a common area for metastasis with surgical treatment as the main modality. Radiotherapy is less utilised in this setting with uncertainty over deliverability and efficacy. Here, we present the details and outcomes of 20 patients treated with radiotherapy, with or without systemic therapy, for melanoma adrenal metastasis in a single institute. Twenty patients were identified from radiation treatment and medical records from between 2015 and 2019 at our institution. Three patients had bilateral radiotherapy treatments and therefore 23 adrenal lesions were analysed. Demographics, indications for treatment, radiotherapy methodology and outcomes were recorded. Outcomes were based on serial 18 F FDG PET/computerized tomography scans reporting using the PERCIST criteria. The most common indication for radiotherapy was oligo-progressive disease (70%) followed by symptom palliation. Eight (35%) of the treatments were delivered by stereotactic ablative body radiotherapy. Twelve (60%) patients had concurrent immunotherapy. Twenty of twenty-three (87%) adrenal lesions had an initial response to treatment with 12 (60%) maintaining local control until death or end of follow-up. Median adrenal-specific progression-free survival was 13 months. Four patients (17%) required salvage adrenalectomy. Symptom palliation was achieved in the majority of patients for which it was indicated and there were no grade three toxicities. The median time from radiotherapy to change of immunotherapy treatment was 4 months. Radiotherapy for melanoma adrenal metastasis is effective and deliverable. With the majority of patients achieving a palliative and clinically relevant durable response, adrenalectomy can be reserved as a salvage option.